Employing Educational Poetic Songs as Grammatical Rules in the Achievement of Fifth Grade Students in Arabic Grammar and Measuring Their Concentration Intensity - Al-Khafaji, Abdul Hussein Ahmed; Al-saedi, Zafar Adel (Journal of Ecohumanism, 2025)
The aim of the current study is to know "the employment of educational poetic songs as grammatical rules in the achievement of fifth-grade students in Arabic grammar and measuring the intensity of their concentration " by validating the follow null hypothesis: There is no statistical sign difference at the stage of sign (0.05) between average achievement of the grades of the experimental group students who study Arabic grammar with educational poetic songs as grammatical rules, and the average achievement of the grades of the control groups students who studied the same subjects in the usual way. There is no statistical sign difference at the stage of sign (0.05) between the average degrees of the experimental group students who study Arabic grammar with educational poetic songs as grammatical rules, and the average scores of the control group students who study Arabic grammar in the usual way of measuring the intensity of concentration (dimensional), to achieve the goal of the study, the researchers chose an experimental design with partial control of the two study groups (experimental and control), and the researchers intentionally chose a school (Khawla Bint Al-Azwar Primary School for Girls) of the Directorate of Education of Diyala Governorate / Khalis District and included three divisions for the fifth grade of primary school, and in a random withdrawal manner Division (A) was chosen to represent the students of the experimental group that studied according to the method of educational poetic songs, while the Division (C) represents the students of the control group that studied according to the usual method (inductive), and has reached The study sample is (54) pupils of the fifth grade of primary school by (27) students for the experimental group and (27) students for the control group. The researchers formulated (62) behavioral objectives covering the five topics specified for the experiment and scheduled to be taught in the second semester, and prepared teaching plans for the five topics and the number was (10) plans by five plans for the experimental groups and five plan for the control groups and presented two of them to a group of experts and specialist in language and method of teaching Arabic, and in the lights of their opinion, the researcher made the necessary adjustments and won the approval of experts. The researchers compared the experimental and control groups using the T-test in the variables (the chronological age of the students, the grades of the previous year in Arabic grammar, and the use of the chi-box in the academy achievement of parent). The studiers, with the assistance of another researcher, ensured that the students in the two study groups received instruction based on the study material's content, which included five topics from the Arabic grammar book for the second semester of the academic year (2023-2024). The researchers used the achievement test as a tool for study, which consisted of (30) items of the type (multiple choice in the blanks of the difference between two sentence order words), as well as the codified Vienna system test consisting of (30) items. The researchers also used statistic mean, including the law of T-test), for 2 independents models, and the chi-square, and the coefficient of difficulty, and discriminatory force, and Alvakronbach) and after statistical processing it turned out that the result of the study is (the existence of a statistically significant difference in favor of the experimental groups at the stage of sign (0.05), and in lights of the result of the study was reached some conclusions, including: 1 - The use of the method of poetic songs educational rules grammatical in the teaching of student of the 5th stage of primary schools came with better results than the use of the usual method.The method of poetic songs and educational grammar rules helped to raise the levels of students with a low scientific level relatively required, i.e., stimulated their interaction, which led this method to raise the scientific level of them. In light of the results of the study, the researchers recommend several recommendations, including:The need for teachers of the Arabic language to use educational poetic songs as grammatical rules in the primary stage, especially for student of the 5th stage of primary schools because of their positive impact on the scientific level of students.Holding seminars or lectures for students of the College of Basic Education in the third and fourth stages on the modern methods and strategies that have been studied, as these two stages are ready for application in schools, to complement the requirements of the study, the researchers proposed several proposals, including: Conducting a study similar to the current study on other grades of the same stage.Conducting a study similar to the current study on variables other than achievement, such as development, acquisition, information retention, and others.